Shaping digitalization among German tourism service providers: Processes and implications - Hannes Thees; Elina Störmann; Franziska Thiele; Natalie Olbrich (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: This study addresses the digital transformation in tourism, accelerated due to the COVID-19 pandemic. By linking the front- and backstage activities, a model of the tourism value system is sketched with the aim to assist the shift toward digital value creation in the case of the German tourism sector by asking, What are the challenges for the digital transformation of tourism service providers, and how can it be promoted along with the tourism value system? Methods: Recognizing the processual challenges of digitalization, this contribution builds upon a mixed-methods approach. First, a quantitative online survey (n = 372) was conducted by the German Competence Center for Tourism at the beginning of the COVID-19 pandemic. The results were discussed in a workshop with 40 experts from the tourism industry in September 2020, where the COVID-19 pandemic was referred to. Results: The focus of tourism service providers is predominantly the digitalization of guest communication, whereas corporate strategies on digitalization are widely not available. Key findings of the survey indicate that competitiveness in digitalization will depend on the appropriate infrastructure, clear strategies, and organizational integration. Implications: The study affirms the increased speed of digital transformation against the backdrop of the COVID-19 pandemic and reveals the need for greater focus on internal processes. In addition, an orchestrated linking of the service providers in a digital ecosystem that is supported by national efforts is proposed.
Keywords: L83; N7; Z30; 330; Digital transformation; German tourism service providers; digital tools and value creation; digitalization of the tourism value system; knowledge gap